Highly reversible Li metal anode using a binary alloy interface. Issue 97 (16th November 2022) - Chen, Jiahe; Sun, Zejun; Li, Zhendong; Liu, Jun; Yao, Xiayin; Peng, Zhe
Abstract : A binary Ag–Zn alloy interface is designed to efficiently enhance the structural stability in keeping the high Li affinity of the alloy structure, and exhibits a great Li protective ability for a stable and durable Li metal anode. Abstract : Suppressing lithium (Li) dendrite growth is a central issue for achieving stable Li metal batteries (LMBs). Here, we propose a binary alloy interface that consists of Ag inner nucleation cores and Zn outer diffusion shells through which a Li solubility gradient is created appropriately to enable simultaneous high lithiophilicity and stability. These merits provide the superior cycling stability of the as-generated Li–Ag–Zn electrode compared with the bare Li or Li–Ag counterparts, resulting in the long-term cycling stability of LMBs.